A validation study of the Self-Efficacy for Strategic Learning in Biology Scales (SESLBS) - Ying Wang; Rayne A. Sperling; Philip M. Reeves (International Journal of Educational Research Open, 2023)
In the present study, we developed and established new self-efficacy scales for students’ strategic learning in undergraduate biology. We used exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to examine the psychometric properties of a new self-efficacy instrument, the Self-Efficacy for Strategic Learning in Biology Scales, that assesses college students’ learning processes in biology. College students enrolled in two introductory-level biology courses were included in our study (N1 = 557; N2 = 447). Both EFA and CFA results demonstrated a two-factor solution for the instrument including students’ self-efficacy for higher-level and lower-level strategic learning processes. We further conducted a longitudinal measurement invariance analysis and scalar invariance was attained across time. Findings demonstrated sound psychometric properties and provide initial validity evidence to support the use of the new measure and subscales.